Investment opportunities - Gold & other precious metals - Jakoubek, Marek (2018)
This thesis is focused on the comparison of gold and other precious metals from an investment point of view. At first, gold, silver, platinum and palladium will be introduced individually and some general information about each metal will be presented. Then, I will be looking into the metals’ price development and comparing one another to observe their behaviour in time. There will also be a chapter about the alternatives to investing into precious metals and stocks. One of the main goals of this thesis will be to show how the prices of metals react in times of economic growth as well as during crises. To accomplish that, I will be analysing the relation between metals and stocks, specifically the famous S&P 500 stock index, and I will be measuring the results based on various criteria. Lastly, I will calculate and present how an optimal portfolio would look like during different periods, based on my findings.